2021
DOI: 10.1590/0103-8478cr20190811
|View full text |Cite
|
Sign up to set email alerts
|

Autologous platelet-rich plasma action on skin autografts in horses

Abstract: This study evaluated the action of autologous platelet-rich plasma (PRP) on cutaneous wounds, containing skin autografts, in the gluteal region of horses. Seven healthy horses were used. Two 6 x 6cm cutaneous wounds were produced on each side of the gluteal region. Eight days after wound induction, grafts were performed with skin fragments harvested from the neck, as well as the application of PRP, prepared by double-centrifugation protocol. Wounds with autografts on the left side received PRP (group T), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Platelet-rich fibrin (PRF) has been investigated in the context of plastic and reconstructive surgery in humans, with demonstrated safety and efficacy to enhance epithelialisation rates and reduce pain at the grafting site (Straub et al, 2022;Vaheb et al, 2021). The use of PRF and platelet-rich-plasma (PRP) in equids has also shown potential benefits in wound healing and skin grafting (da Pedroso et al, 2021;Hamed et al, 2019), although further studies are indicated related to application in specific contexts in veterinary medicine (Soares et al, 2021). In addition, stromal cell-based therapies have been shown to increase graft survival rates by effectively attenuating inflammatory responses (Luo et al, 2019;Xu et al, 2012;Zografou et al, 2011Zografou et al, , 2013.…”
Section: Regenerative Therapiesmentioning
confidence: 99%
“…Platelet-rich fibrin (PRF) has been investigated in the context of plastic and reconstructive surgery in humans, with demonstrated safety and efficacy to enhance epithelialisation rates and reduce pain at the grafting site (Straub et al, 2022;Vaheb et al, 2021). The use of PRF and platelet-rich-plasma (PRP) in equids has also shown potential benefits in wound healing and skin grafting (da Pedroso et al, 2021;Hamed et al, 2019), although further studies are indicated related to application in specific contexts in veterinary medicine (Soares et al, 2021). In addition, stromal cell-based therapies have been shown to increase graft survival rates by effectively attenuating inflammatory responses (Luo et al, 2019;Xu et al, 2012;Zografou et al, 2011Zografou et al, , 2013.…”
Section: Regenerative Therapiesmentioning
confidence: 99%